211k views
2 votes
finitions of f(x) and g(c) below, find the valuef(x) = x2 – 63 - 66x 6g(x) = -3x + 11gx=Submit Answer

finitions of f(x) and g(c) below, find the valuef(x) = x2 – 63 - 66x 6g(x) = -3x + 11gx-example-1
User Asherber
by
4.7k points

1 Answer

1 vote

Given:


\begin{gathered} f(x)=x^2-6x-6 \\ \\ g(x)=-3x+11 \end{gathered}

Find-: g(f(5))

So:


\begin{gathered} g(x)=-3x+11 \\ \\ g(f(x))=-3(x^2-6x-6)+11 \\ \\ g(f(x))=-3x^2+18x+18+11 \\ \\ g(f(x))=-3x^2+18x+29 \end{gathered}

So the value of g(f(5))


\begin{gathered} g(f(x))=-3x^2+18x+29 \\ \\ g(f(5))=-3(5)^2+18(5)+29 \\ \\ g(f(5))=(-3*25)+(18*5)+29 \\ \\ g(f(5))=-75+90+29 \\ \\ g(f(5))=-75+119 \\ \\ g(f(5))=44 \end{gathered}

So the value of g(f(5)) is 44

User Chuprin
by
4.4k points